Effectiveness of isometric muscle training combined with manual lymphatic drainage on secondary lower extremity lymphedema following gynecologic cancer surgery - Ma, Jiahui; Wang, Hewei; Li, Yilan; Guo, Xiang; Xie, Mengjia; Wang, Xinxin; Mao, Luxi; Xing, Dapeng; Shen, Li; Chen, Dan; Wang, Jingxin (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTo investigate the effects of isokinetic strength training combined with manual lymphatic drainage (MLD) on leg circumference, walking ability and muscle strength in patients with secondary lymphedema following gynecologic cancer surgery.DesignRandomized controlled trial.SettingInpatient rehabilitation department.ParticipantsSixty-six patients with secondary lymphedema of the lower extremities following gynecologic cancer surgery were randomly allocated into an experimental group and a control group, each comprising 33 patients.InterventionsThe control group participated in a 4-week standardized MLD program. In addition to the MLD program, participants in the experimental group received additional isokinetic strength training for 20 min daily over the same 4-week period.OutcomesLower limb volume derived from the circumference measurements, Holden Gait Scale and Lovett muscle strength grading.ResultsPrior to the intervention, no statistically significant differences were observed between the two groups across all outcomes (P > 0.05). Post-intervention, statistically significant improvements were noted in the experimental group compared to the control group with respect to reduced lower extremity volume, improved walking ability, and increased muscle strength (P < 0.05).ConclusionFor patients with secondary lower limb lymphedema following gynecological tumor surgery, a combination of isokinetic strength training and MLD has been found to be more effective than MLD alone in reducing edema, improving walking ability, and enhancing muscle strength.